Haematological Malignancies in Systemic Sclerosis Patients: Case Reports and Review of the World Literature - M. Colaci; D. Giuggioli; C. Vacchi; C. Ferri (Case Reports in Rheumatology)
Background. The association of systemic sclerosis (SSc) and haematological cancers was reported in a large number of case reports and cohort studies, describing SSc patients with highly heterogeneous clinical pictures. Objective. We reviewed the literature to better describe SSc patients with haematological malignancies. Methods. SSc cases complicated by haematological malignancies described in the world literature were collected; other 2 cases referred to our centre were reported. Results. One hundred-thirty SSc subjects were collected from 1954 up to date. The mean age of patients at cancer diagnosis was 56.1 ± 16.7 years; 72% of patients were females. In 60% of cases, the diagnosis of haematological malignancy was described within 5 years of SSc diagnosis. In 7.8% of cases, coexistence of Sjögren’s syndrome or other autoimmune disorders was cited. Sixty-six cases with lymphoma (in the majority of cases B-cell neoplasms), 28 with leukaemia (chronic lymphocytic form in 9), 14 with multiple myeloma plus one solitary IgM plasmocytoma, and 16 with myeloproliferative disorders were found. No specific SSc subsets seem to be related to haematological malignancies. Conclusions. We remarked the importance of clinical work-up in SSc, in order to early diagnose and treat eventual occult haematological malignancies, especially during the first years of the disease.